Macroscopic brain region and network changes in a central-arterial-stiffness rat model - Taichi Goto; Yumiko Watanabe; Keigo Hikishima; Ichiro Takashima; Nobuo Kunori (Brain Research Bulletin, 2025)
Cardiovascular disease is a major risk factor for dementia. However, how abnormalities in the cardiovascular system affect the brain remains unclear. By developing a rat model of central arterial stiffness via calcification of the aortic arch, we aimed to investigate the effects of arterial stiffening on the brain, particularly its structures, using ex vivo magnetic resonance imaging. Calcification was induced by applying calcium chloride to the aortic arches of the rats. Similar to physiological findings, such as blood pressure, the model animals exhibited no differences in brain volume. Ex vivo diffusion tensor imaging revealed microstructural changes in the limbic region, including the hippocampus. Analysis of the whole-brain structural connectome showed that the model animals exhibited changes in neural connections, including hippocampal-related networks. These results suggest that central arterial stiffness directly causes structural changes in the limbic regions, including the hippocampus.